PENGARUH REWARD DAN PUNISHMENT TERHADAP MOTIVASI DAN KINERJA PERSONEL SATLANTAS POLRES LOMBOK TENGAH - Marully Rachmat Azwar; Meutia Meutia; Ketut Budiastra (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
The performance of Central Lombok Police Satlantas personnel greatly affects the quality of service to the community, especially in Central Lombok Regency in dealing with local and international events. The purpose of this study was to examine the impact of reward and punishment on the motivation and performance of Central Lombok Police Satlantas personnel. This research is a quantitative research. Research respondents are 69 people who are personnel of the Central Lombok Police Satlantas and also as a sample. The data analysis method used is descriptive data analysis and path analysis to help explain the direction and magnitude of the influence of extrinsic variables on intrinsic variables clearly. The results showed that the higher the reward given, the higher the personal motivation of the Central Lombok Police Traffic Unit, which means that the reward has a significant influence on the personal motivation of the Central Lombok Police Traffic Unit. The higher the punishment given, the higher the personal motivation of the Central Lombok Police Traffic Unit, which means that the punishment has a significant influence on the personal motivation of the Central Lombok Police Traffic Unit. The higher the reward given, the higher the personal performance of the Central Lombok Police Satlantas, which means that the reward has a significant influence on the personal performance of the Central Lombok Police Traffic Unit. The higher the Punishment given, the higher the personal performance of the Central Lombok Police Traffic Unit, which means that the Punishment has a significant influence on the Central Lombok Police Traffic Unit's personal performance. The higher the motivation given, the higher the personal performance of the Central Lombok Satlantas Polres, which means that motivation has a significant influence on the Central Lombok Police Satlantas personal performance.